The Influencing Factors of Customer Satisfaction of O2O Food Takeout Platforms – A Social Institutional Environment Perspective - Hu, Xinyuan; Li, Juan; Wang, Yiting; Qu, Yi (Journal of Asian Business Strategy, 2022)
Online-to-offline (O2O) takeout platforms have become an important way of food consumption in modern life. However, some problems, such as unlicensed operation and poor service, have been exposed. Therefore, it is very important to identify the factors that affect customer trust and satisfaction. However, there are very few studies on consumer satisfaction of takeout platforms in the existing literature. This paper builds a model according to the development of the O2O takeout industry and verifies it by questionnaires and web crawler data. Finally, SPSS data analysis software is used to analyze the variables. The results show that internal mechanisms and social environments affect the trust of users regarding O2O platforms. Also, with the improvement of users’ trust, their perceived level of risk will decline, and their satisfaction will increase. Finally, suggestions of optimizing the platform mechanisms and improving service quality and attitude are advised.